E-KAMUS TEMATIK AJURUMIYAH : MODERNISASI KITAB TRADISIONAL UNTUK SANTRI MILENIAL (Universitas Negeri Semarang, 2023)
This research is motivated by the difficulties of students in understanding the Ajurumiyah book, which is caused by ignorance of the meaning of the vocabulary or terms described in the Jurumiyah book. The limited time in teaching and learning activities at Madrasah Diniyah also affects the level of student's understanding, so the development of an e-dictionary based on an android application is needed to improve the understanding and learning motivation of millennial students. Therefore, the researcher offers a solution by developing a thematic e-dictionary for the vocabulary of the Ajurumiyah book for students of Madrasah Diniyah with the ADDIE model of R&D research design. This research shows that the needs for development of Ajurumiyah book are form of an application with an attractive design. This e-dictionary can be run on smartphones with the Android operating system without using an internet connection. the validation analysis by Expert and teacher about the product shows that this e-dictionary product is good and worth to use, with score 84.2.